2008
DOI: 10.1093/hmg/ddn244
|View full text |Cite
|
Sign up to set email alerts
|

The in vivo mitochondrial two-step maturation of human frataxin

Abstract: Deficiency in the nuclear-encoded mitochondrial protein frataxin causes Friedreich ataxia (FRDA), a progressive neurodegenerative disorder associating spinocerebellar ataxia and cardiomyopathy. Although the exact function of frataxin is still a matter of debate, it is widely accepted that frataxin is a mitochondrial iron chaperone involved in iron-sulfur cluster and heme biosynthesis. Frataxin is synthesized as a precursor polypeptide, directed to the mitochondrial matrix where it is proteolytically cleaved by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
152
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(156 citation statements)
references
References 48 publications
3
152
0
1
Order By: Relevance
“…The transgenic lines U87-FXN and U87-Neo showed patterns, which were identical for all markers analyzed, proving these cell lines to be derivatives of U87MG cells, which had been originally obtained from the ATCC. Three of these markers, amelogenin (X), vWA (alleles 15,17) and THO1 (allele 9.3) are published for the parental line U87MG in the ATCC database (http://www.ATCC.org). OLN-93 was originally derived from a primary rat brain glial culture and resembles primary oligodendrocytes.…”
Section: Cell Culturementioning
confidence: 99%
“…The transgenic lines U87-FXN and U87-Neo showed patterns, which were identical for all markers analyzed, proving these cell lines to be derivatives of U87MG cells, which had been originally obtained from the ATCC. Three of these markers, amelogenin (X), vWA (alleles 15,17) and THO1 (allele 9.3) are published for the parental line U87MG in the ATCC database (http://www.ATCC.org). OLN-93 was originally derived from a primary rat brain glial culture and resembles primary oligodendrocytes.…”
Section: Cell Culturementioning
confidence: 99%
“…In human cells, the presence of an extramitochondrial form of frataxin has been reported that could be involved in IRP1 regulation (42). It should be noted, however, that the existence of such an extramitochondrial form of frataxin has been questioned by other authors (43). To analyze the existence of such an extramitochondrial form of Yfh1, yeast cells carrying an HA-tagged Yfh1 (strain BQS204) were fractionated and analyzed by Western blot for the presence of Yfh1-HA in the cytosolic and mitochondrial fractions (Fig.…”
Section: Analysis Of Iron Accumulation and Aconitase Activity On Thementioning
confidence: 99%
“…In this organelle, the protein is first processed to the intermediate , and then to the mature form, FXN 81-210 [1,2]. Mature FXN plays an essential role in iron homeostasis; it may act as an iron chaperone delivering iron to enzyme partners during heme and Fe-S cluster biosynthesis [3][4][5].…”
Section: Introductionmentioning
confidence: 99%